PENGEMBANGAN MEDIA UNBIL MODEL KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS 3 SD NEGERI TLOGO 02 BLITAR - Novitasari, putri; Nur Amalia, Shofi; Tri Oktaviani, Ragil (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2025)
This study aims to develop an innovative learning medium in the form of a card game called UNO Bilangan (UNBIL), integrated with the Student Teams Achievement Division (STAD) cooperative learning model. The primary objective of this development is to improve the numeracy skills of third grade elementary school students, particularly in addition and subtraction of whole numbers. The background of this study is based on the limited use of concrete learning media in mathematics instruction, low student learning motivation, and teachers’ difficulties in designing creative and engaging instructional media. The research method employed was Research and Development (R&D) using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were third-grade students of SD Negeri Tlogo 02 Blitar. Data collection instruments included expert validation questionnaires, teacher feasibility questionnaires, and pretest and posttest assessments to measure students’ learning improvement. The results indicate that the UNBIL learning media meets the criteria of validity and feasibility based on evaluations from experts and educational practitioners. The effectiveness of the UNBIL media in enhancing students’ numeracy skills was demonstrated through N-Gain analysis, which yielded an average score of 0.73, categorized as high according to Hake’s criteria (1999). This finding suggests that the integration of UNBIL media with the STAD learning model is effective in improving students’ learning outcomes in whole number topics. In conclusion, UNBIL learning media based on the STAD model serves as an effective, innovative, and engaging alternative for mathematics instruction in elementary schools, contributing to increased student participation and conceptual understanding.